Determinants Of Sharia Bank Customer Loyalty In Indonesia: Study Of Literature And Student Response Of Postgraduate Sharia Banking (International Journal of Cultural and Social Science, 2022)
In an effort to realize customer loyalty to Islamic banks, it is necessary to realize the determinants of customer loyalty of Islamic banks. This study aims to determine what factors determine the loyalty of Islamic bank customers in Indonesia. This research was conducted using qualitative research methods, namely content analysis of papers from the google schoolar database and interviews using in-depth interview techniques. The results showed that the factors that influence the loyalty of Islamic bank customers are action, attitude, attention, corporate image, customer bonding, customer relationship, customer social responsibility, determinants of brand equity, good corporate governance, price, employees, emotional intelligence, intelligence. intellectual, spiritual intelligence, trust, customer satisfaction, commitment, communication, service quality, Islamic service quality, location, customer value, conflict handling, perceived value, product, professionalism, promotion, religiosity, social responsibility and transparency. The results of interviews with Islamic Banking Graduate Students there are other factors that determine customer loyalty, namely bank guarantees and legality.